2011
DOI: 10.1371/journal.pone.0025805
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Circuitry Associated with Exploratory Eye Movement in Schizophrenia: A Voxel-Based Morphometric Study

Abstract: Schizophrenic patients present abnormalities in a variety of eye movement tasks. Exploratory eye movement (EEM) dysfunction appears to be particularly specific to schizophrenia. However, the underlying mechanisms of EEM dysfunction in schizophrenia are not clearly understood. To assess the potential neuroanatomical substrates of EEM, we recorded EEM performance and conducted a voxel-based morphometric analysis of gray matter in 33 schizophrenic patients and 29 well matched healthy controls. In schizophrenic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 71 publications
1
43
0
Order By: Relevance
“…Furthermore, the cuneus (BA 18, 19), which is most known for its involvement in basic visual processing (Delvecchio et al, 2013; Qiu et al, 2011), also occur in fMRI and sMRI. Since MCCB experiments include visual learning and attention tasks, it makes sense to identify the visual cortex as part of cognition prediction, and many studies have discovered that SZs present visual processing abnormalities in a variety of tasks (Hardoy et al, 2004; Qiu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the cuneus (BA 18, 19), which is most known for its involvement in basic visual processing (Delvecchio et al, 2013; Qiu et al, 2011), also occur in fMRI and sMRI. Since MCCB experiments include visual learning and attention tasks, it makes sense to identify the visual cortex as part of cognition prediction, and many studies have discovered that SZs present visual processing abnormalities in a variety of tasks (Hardoy et al, 2004; Qiu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Since MCCB experiments include visual learning and attention tasks, it makes sense to identify the visual cortex as part of cognition prediction, and many studies have discovered that SZs present visual processing abnormalities in a variety of tasks (Hardoy et al, 2004; Qiu et al, 2011). Moreover, the similar covariation between fMRI and sMRI suggests a synchronicity and complementary nature between structural and functional changes in cognitive impairment of schizophrenia, which is supported by (Casey et al, 2005; Salgado-Pineda et al, 2004; Schultz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…ment parameters of the eye such as central corneal thickness (CCT), ACV, ACD, LT, and CV. Some ocular problems in schizophrenic patients such as dysfunction of saccadic eye movements and stereopsis disorders (particularly in schizophrenic patients with visual hallucinations) have been reported in the literature (23,24) . Recently, Meier et al demonstrated a mi crovascular abnormality in schizophrenia by retinal imaging (25) .…”
Section: Discussionmentioning
confidence: 99%
“…The primary visual cortex (BA 17) processes sensory information from the ipsilateral lateral geniculate nucleus integrating the spatiotemporal features of vision. Information is then relayed from this site to the associated visual cortices which are involved with processing aspects of visual information including object recognition (BA 18) and shape recognition and multisensory integration (B19) (though these processes do not appear isolated to one region) (see [43]). Thus the BA specific changes observed in our study may aid in the explanation of why discrete changes to visual acuity are seen in children whose mothers smoked [28].…”
Section: Discussionmentioning
confidence: 99%
“…While these areas are adjacent to one another and are all involved in visual processing, they subserve different aspects of this function -primary (BA 17) versus associative (BA 18 and BA 19) (see [43]). We hypothesized that exposure of the baboon fetus to exogenous nicotine would alter the binding to its receptors depending upon nAChR subunit composition and BA (primary versus associative) in the occipital cortex as measured by tissue receptor autoradiography.…”
Section: Introductionmentioning
confidence: 99%